2000
DOI: 10.1111/1467-8535.00134
|View full text |Cite
|
Sign up to set email alerts
|

Implementation strategies for educational intranet resources

Abstract: Recent events in UK Higher Education have caused university schools to look toward alternative means of enhancing and monitoring the quality of the service they provide. One approach utilises networked learning and teaching resources, in particular intranets. Two Schools at the University of Brighton commenced independent implementation of intranets at similar times. The subjects of the case studies are the School of Pharmacy and Biomolecular Sciences Intranet (SPI) and the Business School Intranet (BSI). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
2
10
0
Order By: Relevance
“…Where it appears both groups value this condition when implementing a technology innovation, those in K-12 settings consider the condition more important than do those in higher education and business settings. These findings support earlier research on implementation of technologies in K-12 settings (e.g., Bauder, 1993;Dalton, 1989;Ebersole & Vorndam, 2003;Herson, et al, 2000;Ravitz, 1999). Individual group comparisons for the condition participation indicated a significant difference between the K-12 group and the business group (p < .05).…”
Section: Technology Form Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Where it appears both groups value this condition when implementing a technology innovation, those in K-12 settings consider the condition more important than do those in higher education and business settings. These findings support earlier research on implementation of technologies in K-12 settings (e.g., Bauder, 1993;Dalton, 1989;Ebersole & Vorndam, 2003;Herson, et al, 2000;Ravitz, 1999). Individual group comparisons for the condition participation indicated a significant difference between the K-12 group and the business group (p < .05).…”
Section: Technology Form Resultssupporting
confidence: 89%
“…This may explain the difference between the scores and importance that the K-12 and higher education placed on resources. This result supports previous research on technology innovations in academic settings that indicated resources were a critical component to implementation (e.g., Bauder 1993;Dalton, 1989;Ebersole & Vorndam 2003;Herson, et al, 2000;Ravitz, 1999;Rogers, 2000).…”
Section: Technology Form Resultssupporting
confidence: 88%
See 3 more Smart Citations